An effect of homology length on gene disruption in Neurospora crassa - Y. Nakanishi; C. Ishii; H. Inoue (Fungal Genetics Reports, 2005)
For targeted gene disruption in wild-type Neurospora crassa, 1000-bp of homologous sequences on either side of the cassette used for disruption is sufficient to give more than 10 % homologous recombination. We report here that varying the length of homology on each side seems to have different effects on the homologous recombination frequency.